BUSINESS RESILIENCE STRATEGIES IN ORGANIZATIONS IN AN ERA OF UNCERTAINTY: A SYSTEMATIC LITERATURE REVIEW - Khoiri, Moh. (Resilience of Small Medium Business, 2025)
Objective: This study aims to develop an evidence-based synthesis of business resilience strategies adopted by organizations operating in an era of uncertainty during 2016–2025, with particular attention to how resilience is defined, operationalized, and translated into actionable strategy bundles across disruption phases. Research Design & Methods: A Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines. Literature was retrieved from major academic databases (Scopus, Web of Science, ScienceDirect, Emerald Insight, SpringerLink, Google Scholar, and national databases), screened using predefined inclusion or exclusion criteria, and assessed through a three item quality appraisal (QA1–QA3). Fifteen peer-reviewed studies published between 2016 and 2025 were included and synthesized using descriptive mapping and thematic analysis. Findings: The review shows a clear conceptual shift from resilience as a post-disruption outcome toward resilience as a capability-based, dynamic, and multi-level construct. Strategies are rarely isolated; instead, they form cross-domain bundles spanning governance or BCM, operations and supply chain continuity, financial buffering, human capital, and digital adaptation. The synthesis supports a sequenced pathway in which business continuity management (BCM) enables operational resilience by stabilizing critical functions, which subsequently supports organizational resilience through learning, resource reconfiguration, and strategic renewal. Strategy effectiveness is contingent on disruption type and pre-crisis organizational capacity. Implications & Recommendations: Organizations should adopt a staged resilience roadmap, strengthen BCM maturity, invest in operational continuity capabilities, and institutionalize learning-based renewal mechanisms. SMEs should prioritize cashflow discipline, network access, and scalable digital pivots aligned with resource constraints. Contribution & Value Added: This study clarifies construct boundaries by proposing a mechanism-based integration of business continuity management (BCM), operational resilience, and organizational resilience, thereby offering a structured and actionable framework for both research and practice.